Micro-texture and in situ sulfur isotope of pyrite from the Baiyunpu Pb–Zn deposit in central Hunan, South China: Implications for the growth mechanism of colloform pyrite aggregates. (15th May 2020) - Huang, Fei; Gao, Shang; Chen, Lei; Su, Limin; Li, Yongli; Meng, Lin; Liu, Kaijun; Chai, Chenwei; Qi, Xinyi
Graphical abstract: Highlights: Colloform pyrite has a concentric-banded texture with the core composed of granular microcrystals ( 300 nm). Colloform pyrite has abrupt changes between a random CPO and <100>, or <110> CPOs. The growth of pyrite transform from disordered microcrystals into elongated crystals is controlled by geometrical selection. Abstract: Colloform pyrite textures have been detected in various geological bodies and have received much attention in recent years. Although these textures have been proved to be formed by the aggregation of micro-grains with different sizes, further work is needed to understand the mechanism for developing them. We carried out a detailed study on the micro-textures, crystal preferred orientations (CPOs), trace element, and sulfur isotope compositions of colloform pyrite aggregates from the Baiyunpu Pb–Zn deposit in Hunan, China. Results showed that the inner core of colloform pyrite had an irregular outline with flattening at their contact boundaries and was commonly formed by the compaction of multiple spherical aggregates. The outer layers concentrically grew around the core. Field emission-scanning electron microscope (FE-SEM) suggested both the inner core and the outer layers were composed of a large number of nano- or micron-scale grains ( 300 nm granular crystals to acicular and elongated crystals up to 100 μm in length). Electron backscatter diffraction (EBSD) revealed an initial random CPO in the core and either 〈1 0 0〉 or 〈1 1 0〉 CPOs in subsequent layers. In situ sulfur isotope compositions obtained by secondary-ion mass spectrometry (SIMS) showed that the δ 34 S values of colloform pyrite ranged from −8.4 to −0.2‰, which were interpreted to be mainly derived from thermochemical sulfate reduction (TSR). Colloform pyrite aggregates are considered to grow from the core outward through the accretion of layers, including (1) formation and aggregation of microcrystals in core A1 and (2) growth and geometrical selection of crystals in outer layers. The growth and transformation of pyrite from disorderly granular microcrystals in the core to elongated crystals radiating from the aggregated center in the outer concentric zones is thought to be controlled by geometrical selection. Factors affecting the epitaxial relationship between the substrate and the growing crystals, such as interface energy, ambient temperature and degree of sulfur supersaturation, may control the abrupt changes in CPO recorded in colloform pyrite aggregates.